A review of the current state of abrasive water-jet turning machining method - Kartal, Fuat (Springer Science and Business Media LLC, 2016)
Abrasive water-jet turning (AWJT) is one of these alternative methods and has gained an important status among others in a very short period of time. AWJT becomes prominent with its flexibility in cutting materials with almost any properties, with the elimination of thermal effects during the process, and with minimal stresses it imposes. It is widely preferred when heat-affected zones are to be avoided as it is a cold process. AWJT, on the other hand, is the replacement of a traditional cutter head of a turning testing apparatus with the AWJ in order to remove material turning the workpiece using a spindle testing apparatus while moving the nozzle on an axis with a specific distance from the workpiece. It is convenient to machine planar workpieces using the AWJ while it is harder to machine (turn) workpieces. However, there are scientific studies on the machinability of the planar workpieces, studies on the machinability of cylindrical materials are rarely found in the literature. Among the machining parameters for AWJT are nozzle feed rate, spindle speed, abrasive flow rate, pump pressure, abrasive size, and standoff distance. The studies available in the literature focus on the impact on Ra (μm), machining depth (mm), and material removal rate (mm3 min−1) as experiment outcomes. In this study, reviews of the research are available in the literature on the turning of workpieces using abrasive water jet. This study will also discuss the recommendations for the future research.